Sexual dimorphism in Parkinson’s disease: differences in clinical manifestations, quality of life and psychosocial functioning between males and females - Farhadi F (Dove Medical Press, 2017)
Farzaneh Farhadi,1 Kia Vosoughi,1 Gholam Ali Shahidi,2 Ahmad Delbari,3,4 Johan Lökk,3,5 Seyed-Mohammad Fereshtehnejad3,6,7 1Medical Student Research Committee, 2Movement Disorders Clinic, Department of Neurology, Faculty of Medicine, Iran University of Medical Sciences, Tehran, Iran; 3Division of Clinical Geriatrics, Department of Neurobiology, Care Sciences, and Society (NVS), Karolinska Institutet, Stockholm, Sweden; 4Iranian Research Center on Aging, University of Social Welfare and Rehabilitation, Tehran, Iran; 5Department of Geriatric Medicine, Karolinska University Hospital, Stockholm, Sweden; 6Department of Neurology and Neurosurgery, McGill University, Montreal, QC, Canada; 7Firoozgar Clinical Research Development Center, Firoozgar Hospital, Iran University of Medical Sciences, Tehran, Iran Introduction: Sex-related differences in clinical manifestations and consequences of Parkinson’s disease (PD) have been poorly explored. Better understanding of sexual dimorphism in neurologic diseases such as PD has been announced as a research priority. The aim of our study was to determine independent sex differences in clinical manifestations and subtypes, psychosocial functioning, quality of life (QoL) and its domains between male and female individuals with PD.Patients and methods: A comprehensive list of demographics, motor symptoms and subtypes, nonmotor features, health-related quality of life (HRQoL), psychosocial functioning and general aspects of daily life was assessed in 157 individuals (108 males and 49 females) with idiopathic PD. In order to control for potential confounding variables, we applied Orthogonal Partial Least Squares – Discriminant Analysis (OPLS-DA) to explore the strength of each feature to discriminate male and female patients with PD.Results: While no sex difference was found in the total Unified Parkinson’s Disease Rating Scale (UPDRS) score and cumulative daily dose of levodopa, females had significantly more severe anxiety (mean difference =2.2 [95% confidence interval, CI: 0.5–4.0], P=0.011), worse nutritional status (23.8 [standard deviation, SD =4.2] vs 25.8 [SD =2.6], P=0.003) and poorer QoL (28.3 [SD =15.7] vs 17.9 [SD =14.2], P<0.001). Based on multivariate discriminant analysis, emotional well-being, bodily discomfort, social support, mobility and communication domains of HRQoL, together with anxiety, depression and psychosocial functioning, were the strongest features with more severe/worse status in females after adjustment for potential statistical confounders.Conclusion: Our study provides a comprehensive understanding of sexual dimorphism in PD. Anxiety, depression, specific domains of HRQoL (mobility, emotional well-being, social support and bodily discomfort) and psychosocial functioning were significantly worse in female individuals with PD. Sexual dimorphism in PD highlights the features that are more likely to be affected in each sex and should be specifically targeted when managing male and female individuals with PD. Keywords: Parkinson’s disease, sexual dimorphism, male, female, quality of life, psychosocial functioning